A Scientific Approach To Tuak Making Using Rice And Glutinuos Rice - Natasha Leann, Mortima Yorke (Universiti Malaysia Sarawak (UNIMAS), 2022)
Tuak is a rice wine that belongs to the Dayak tribes. It is commonly made using glutinous rice and added with ragi as the starter culture. The biochemicals components, sugar and ethanol profiles as well as the fermentative activities of inoculum in tuak that contributes to tuak qualities has not been fully elucidated. In this study, tuak was produce using a mixture of rice and glutinous rice and added with two types of starter culture; conventional ragi and a starter culture of known fungal culture. The biochemical constituents of tuak during the fermentation was analysed through HPLC analysis, PSA assays and TPC test for 36 days. The results show that tuak added with conventional ragi was able to produced ethanol at 77.6 g/L after 36 days of fermentation while tuak added with the starter culture of known fungal culture was unable to produce ethanol after 36 days of fermentation. In conclusion, the starter culture of known fungal culture were unable to ferment the mixture of rice and glutinous rice in tuak efficiently. This study suggests that different types of starter culture used in tuak fermentation will effects the biochemicals production in tuak, thus contributes to distinct sensory and nutritional qualities of tuak.